A systematic review and Meta-analysis of urinary extracellular vesicles proteome in diabetic nephropathy - Ding, Xiaonan; Wang, Xiaochen; Du, Junxia; Han, Qiuxia; Zhang, Dong; Zhu, Hanyu (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is a major microvascular complication of both type 1 and type 2 diabetes mellitus and is the most frequent cause of end-stage renal disease with an increasing prevalence. Presently there is no non-invasive method for differential diagnosis, and an efficient target therapy is lacking. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptotic bodies, are present in various body fluids such as blood, cerebrospinal fluid, and urine. Proteins in EVs are speculated to be involved in various biochemical processes and reflect the original cells' physiological states and pathological conditions. This systematic review is based on urinary extracellular vesicles (uEVs) studies, which enrolled patients with DN and investigated the proteins in uEVs. We systematically reviewed articles from the PubMed, Embase, and Web of Science databases until January 4, 2022. The article quality was appraised according to the Newcastle-Ottawa Quality Assessment Scale (NOS). The methodology of samples, isolation and purification techniques of uEVs, and characterization methods are summarized. Molecular functions, pathways, and disease-associated genes and variants were enriched in all retrievable uEV proteins from 10 eligible studies. Protein-protein interaction analysis (PPI) revealed marked pathways of significant proteins. A total of 501 articles were identified, and 10 eligible records were selected for further analysis. A total of 651 participants were enrolled, and among the 10 eligible studies, two performed mass spectrometry to obtain the proteome profile. A total of 636 retrievable proteins were identified, of which 28 were identified in two studies, and ceruloplasmin (CP) and dipeptidyl peptidase-IV (DPP4) were identified in three studies. Furthermore, 41 reported significant proteins presented a marked connection with the pathophysiological alterations of DN. These systematic review results show concordance with previous studies and may help overlook the methodology of uEVs in DN patients and deepen the understanding of uEV proteins in DN.